2021
DOI: 10.1523/eneuro.0522-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Vagus Nerve Stimulation on Learning and Evoked Activity in Auditory Cortex

Abstract: Chronic vagus nerve stimulation (VNS) has been shown to facilitate learning, but effects of acute VNS on neural coding and behavior remain less well understood. Ferrets implanted with cuff electrodes on the vagus nerve were trained by classical conditioning on an auditory tone frequency-reward association. One tone was associated with reward while another tone was not. Tone frequencies and reward associations were changed every 2 days, requiring learning of a new relationship. When tones were paired with VNS, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This makes it difficult to disentangle direct VNS effects from changes in arousal. In contrast, another recent work demonstrated a VNSdriven suppression of neural response to an auditory tone that persisted even after arousal state was regressed from the neural response (Lai and David, 2021). Our trial design controls for movement state, and VNS did not produce any noticeable acute motor response.…”
Section: Motor Cortical Neurons Are Modulated By Vns Via Cholinergic ...mentioning
confidence: 66%
“…This makes it difficult to disentangle direct VNS effects from changes in arousal. In contrast, another recent work demonstrated a VNSdriven suppression of neural response to an auditory tone that persisted even after arousal state was regressed from the neural response (Lai and David, 2021). Our trial design controls for movement state, and VNS did not produce any noticeable acute motor response.…”
Section: Motor Cortical Neurons Are Modulated By Vns Via Cholinergic ...mentioning
confidence: 66%
“…In general, these studies have delivered phasic VNS (e.g., 0.5 s, 30 Hz, 0.8 mA, 100 μs biphasic pulses) in pair with a specific sensory stimulus (e.g., a specific frequency auditory tone or tactile tap) repeatedly across multiple sessions (e.g., 300 times/day, 20 days). This alters sensory processing in a manner that facilitates detection of the specific paired stimulus ( Martinez-Vargas et al, 2009 ; Engineer et al, 2011 ; Meyers et al, 2019 ; Darrow et al, 2020 ; Lai and David, 2021 ) and accordingly disfavors detection of non-paired stimuli. This mechanism of action can be strengthened over multiple sessions of pairing to produce long-term permanent reorganization of sensory pathways that alters perception.…”
Section: Lasting Alterations To Sensory Processing Occur Over Time Wh...mentioning
confidence: 99%
“…So, there was no significant difference in neuronal activities between during VNS and pre-VNS baseline. Furthermore, the effects of VNS modulation varied among different parameters, and enhancement of performance of behavior tasks and cortical map plasticity was strongest in response to intermediate intensity of stimulation (Ghacibeh et al, 2006;Lai and David, 2021). Therefore, we concluded that there might be an individual difference in the effects of VNS modulation, and the optimal parameters were crucial to VNS application.…”
Section: Characteristics Of Calcium Signaling Of Neurons In Cerebral ...mentioning
confidence: 75%